Technical and Tactical Training in Student Football Players - Abdimalik o'g'li, Nomozov Suyunbek (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article, the usual methods of physical education in the stages of training young players and improving their skills: exercises, games. Competitive methods, demonstration, use of oral speech, use of error correction techniques are shown.